2019
DOI: 10.1155/2019/6569874
|View full text |Cite
|
Sign up to set email alerts
|

Subthalamic Nucleus Stimulation Does Not Have Any Acute Effects on Verbal Fluency or on Speed of Word Generation in Parkinson’s Disease

Abstract: Background Deep brain stimulation of the subthalamic nucleus (STN-DBS) has been shown to be generally safe from a cognitive perspective, with consistent evidence that the major impact of STN-DBS in Parkinson's disease (PD) is on verbal fluency. Objective The aim of this study was first to identify the influence of acute manipulation of STN-DBS in PD on the number and time pattern of word generation on different verbal fluency (VF) tasks, phonemic, switching, and cued switching, and second to determine whether … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 46 publications
(55 reference statements)
0
2
0
Order By: Relevance
“…Moreover, we studied patients in their optimal medication and stimulation state and did not include a postoperative off stimulation state to dissociate potential surgical lesion from stimulation effects. Two recent studies that investigated the stimulation effect on verbal fluency, by comparing ON‐OFF stimulation performance, did not find a DBS effect 58,59 . Similarly, a review on DBS‐induced cognitive decline 14 suggested that verbal fluency appears to be largely a surgical implantation effect.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, we studied patients in their optimal medication and stimulation state and did not include a postoperative off stimulation state to dissociate potential surgical lesion from stimulation effects. Two recent studies that investigated the stimulation effect on verbal fluency, by comparing ON‐OFF stimulation performance, did not find a DBS effect 58,59 . Similarly, a review on DBS‐induced cognitive decline 14 suggested that verbal fluency appears to be largely a surgical implantation effect.…”
Section: Discussionmentioning
confidence: 99%
“…Two recent studies that investigated the stimulation effect on verbal fluency, by comparing ON-OFF stimulation performance, did not find a DBS effect. 58,59 Similarly, a review on DBS-induced cognitive decline 14 suggested that verbal fluency appears to be largely a surgical implantation effect. Others have pointed out the impact of stimulation parameters and contact location as contributing factors, especially in terms of individual variation in fluency effects.…”
Section: Limitations and Future Directionsmentioning
confidence: 99%